COMPLIMENTING STRATEGIES BY ENGLISH-MAJOR STUDENTS AT THAI NGUYEN UNIVERSITY = Các chiến lược khen ngợi của sinh viên chuyên ngành tiếng Anh tại Đại học Thái Nguyên. M.A Thesis Linguistics: 60 22 15 - Trần, Thị Yến (University of Languages and International Studies, 2017)
48 p. + CD-ROM